CTNI-64. FOCUSED ULTRASOUND MEDIATED BLOOD-BRAIN BARRIER PENETRANCE TO ENABLE CELL-FREE DNA (CFDNA) AS A LIQUID BIOPSY IN RECURRENT PRIMARY BRAIN TUMORS. (14th November 2022) - Miller, Alexandra; Ramamurthy, Bhaskar; Pike, Luke; Keralapura, Mallika; Hofius, Jonathan; Marshall, Jack; Jones, Marvin; Lee, Chi-Yin; Stember, Joseph; Brennan, Cameron; Kaley, Thomas; Dittamore, Ryan; et al.
Abstract: The WHO recommends molecular characterization of CNS tumors. (Louis et al., 2021, 2016). However, many patients at diagnosis and recurrence, do not have tissue accessible for genomics. Blood-based liquid biopsy tests, provide a non-invasive means to obtain genomic data. Liquid biopsy tests are widely adopted to avoid side effects related to invasive biopsies in other solid tumors. However, for primary brain tumors, most patients have cfDNA concentrations below the Limit-of-Detection (LOD) of the tests. The primary contributor to low yield is the blood-brain barrier (BBB) which prevents free passage of tumor analytes into the circulatory system. BBB opening mediated by Focused Ultrasound (FUS) oscillation of microbubbles (MB) has led to an increase of tumor-derived circulating biomarkers in pre-clinical models and in human GBM (Zhu et al 2018, Meng et al 2021). Cordance Medical is developing a non-invasive, portable FUS platform that can enable clinic-based BBB opening treatments. The Cordance device utilizes three transducer types, a Type 1 transducer for non-invasive BBB opening localization obtains Doppler images of the Circle-of-Willis through the temporal lobe. The Doppler images align to the existing MRI using CoW as the fiducial. An array of Type 2 transducers for BBB opening to generate sufficient acoustic pressure to safely oscillate MBs to open the BBB. Finally, Type 3 transducers for safety monitoring receive echo signals from the MBs. Signals are analyzed for harmonic content which enables safety monitoring. The primary endpoint, we will be examining the Cordance platform's ability to increase the concentration of circulating biomarkers following a safe BBB opening. We will recruit patients with recurrent GBM. Patients will receive a baseline blood draw, a BBB opening treatment with the Cordance device, followed by a blood draw after the treatment. Liquid biopsy tests to be examined include the MSK ACCESS test and tumor-informed ddPCR MRD test.